HUBUNGAN LAMA IMPLANTASI STENT DENGAN KEJADIAN IN-STENT RESTENOSIS BERMAKNA PADA PASIEN PJK YANG DILAKUKAN ANGIOGRAFI KORONER EVALUASI DI RUMAH SAKIT UMUM DAERAH PROVINSI NUSA TENGGARA BARAT - Zikriyya Melati Rahmany; Pintaningrum, Yusra; Ermawan, Romi (Faculty of Medicine Universitas Mataram, 2021)
Background : in-stent restenosis is a problem which happens in patient whom underwent percutaneous coronary intervention procedure. The aim of this study is to know the correlation between the duration of stent implantation and significant in-stent restenosis case on coronary heart disease (CHD) patient under coronary angiography evaluation. Method : This study is an observational analytic study with cross sectional method on CHD patient under coronary angiography evaluation in West Nusa Tenggara Public Hospital. The data were obtained from heart catheterization laboratory and medical records from January, 2018 until June, 2020. The analysis was done by eta correlative hypothesis using SPSS Ver. 26.0. Result: This research has 89 subjects. The statistical analysis showed p = 0.174 and r = 0.251 Conclusion: There is no correlation between the duration of stent implantation and significant in-stent restenosis case on CHD patient under coronary angiography evaluation in West Nusa Tenggara Public Hospital. Key Word: In-stent restenosis, the duration of stent implantation, coronary angiography evaluation, coronary heart diasease